Retinoid-X receptor agonism promotes remyelination in relapsing-remitting multiple sclerosis: a phase 2 clinical trial. Issue 6 (27th May 2022) - L Brown, J William; Cunniffe, Nicholas G; Prados, Ferran; Kanber, Baris; Connick, Peter; lin, Robin Frank-; Chandran, Siddharthan; Altmann, Daniel; Chard, Declan T; Coles, Alasdair J
Abstract : Background: In rodents, retinoid acid X receptor [RXR]-gamma agonists promote CNS remyelination. Methods: In this double-blind phase 2a trial, participants with relapsing remitting multiple sclerosis (RRMS), stable on dimethyl fumarate, were randomised to bexarotene 300mg/m2 (a non-specific RXR agonist) or placebo for 6 months. The primary efficacy outcome was change in mean lesional magnetisation transfer ratio (MTR) for lesions below the within-patient median MTR. The secondary efficacy outcome was change in visual evoked potential (VEP) latency in eyes with electrophysiological evidence of optic neuropathy. Results: 52 patients were randomised to bexarotene or placebo. All bexarotene patients experienced adverse effects, notably central hypothyroidism (26 [100%]), hypertriglyceridaemia (24 [92%]), rash (13 [50%]) and neutropenia (10 [38%]). Two discontinued placebo and five discontinued bexarotene through adverse events. The primary efficacy outcome was negative (mean submedian lesion MTR change 0.25pu (bexarotene) vs 0.09pu (placebo), p=0.54), but significant effects were seen in grey matter lesions (p=0.008). Bexarotene reduced VEP latency in those with optic neuropathy (group difference 4·66 ms/eye, p=0·014). Conclusions: Despite a negative primary outcome, we found imaging and electrophysiological evidence of remyelination following RXR agonism in people with RRMS. Bexarotene's safety profile precludes it's use, but these data support selective RXR-gamma agonist development. william.brown@doctors.org.uk